2019
DOI: 10.1136/bmjopen-2019-033940
|View full text |Cite
|
Sign up to set email alerts
|

Reliability and validity of the Japanese version of the Ocular Surface Disease Index for dry eye disease

Abstract: ObjectivesThe Ocular Surface Disease Index (OSDI) questionnaire is widely used to evaluate subjective symptoms of dry eye disease (DED) as a primary diagnostic criterion. This study aimed to develop a Japanese version of the OSDI (J-OSDI) and assess its reliability and validity.Design and settingHospital-based cross-sectional observational study.ParticipantsA total of 209 patients recruited from the Department of Ophthalmology at Juntendo University Hospital.MethodsWe translated and culturally adapted the OSDI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
74
1
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 69 publications
(81 citation statements)
references
References 29 publications
5
74
1
1
Order By: Relevance
“…Symptoms (measured by OSDI) and signs (TMH, meibomian gland expressibility, meibum quality, eyelid margin abnormalities, and corneal staining) as well as corneal nerve condition after IPL treatment were evaluated in our investigation. e OSDI has been reported to be a reliable and valid parameter for discriminating the severity of dry eye diseases [28,29]. We found that the value was significantly decreased after IPL treatment compared with baseline, which is in agreement with other investigators' studies [13,14].…”
Section: Discussionsupporting
confidence: 92%
“…Symptoms (measured by OSDI) and signs (TMH, meibomian gland expressibility, meibum quality, eyelid margin abnormalities, and corneal staining) as well as corneal nerve condition after IPL treatment were evaluated in our investigation. e OSDI has been reported to be a reliable and valid parameter for discriminating the severity of dry eye diseases [28,29]. We found that the value was significantly decreased after IPL treatment compared with baseline, which is in agreement with other investigators' studies [13,14].…”
Section: Discussionsupporting
confidence: 92%
“…Scores are graded from 0-100 in both questionnaires, but the DEQS cannot estimate severity by score unlike the J-OSDI. As for the validity by language, the J-OSDI has been confirmed to be valid in both Japanese and English [16], whereas the DEQS has only been validated in Japanese. As the OSDI is used worldwide, it can be used for comparisons between Japan and other countries.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, the OSDI is commonly used worldwide. The validity and reliability of the Japanese version of the OSDI (J-OSDI) were confirmed by Inomata et al in 2019 [16], and it became possible to perform epidemiological and symptomatic comparisons of DED between Japan and other countries. The J-OSDI and DEQS are now available as validated dry eye questionnaires in Japan, but the purpose of both these dry eye questionnaires are different, and both questionnaires have pros and cons.…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation
“…The OSDI total score can be used to classify the respondent's dry eye symptoms as normal (0-12 points), mild (13-22 points), moderate (23-32 points), or severe (33-100 points) [30][31][32]. This questionnaire was originally developed in English [29] with subsequent translations and validations in Portuguese [33], Spanish [34], Farsi [35], Bahasa [36], Chinese [37], Filipino [38], and Japanese [39]. However, caution should be applied when using it, given that the cutoff values for DED differ across languages, with a threshold of 27.2 and 36.3 points in the Chinese and Japanese versions, respectively [37,39,40].…”
Section: Ocular Surface Disease Index (Osdi)mentioning
confidence: 99%